2019
DOI: 10.21660/2019.63.48112
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Joint Surface Roughness of Two Natural Rocks During Shearing

Abstract: This study seeks to investigate the effect of joint surface damage on the shear strength of two natural rocks, namely sandstone and argillite. A series of shear box tests were performed on the jointed rock specimens with different joint roughness coefficients (JRC). The joint surface roughness of each rock specimen was estimated by means of Barton's comb before and after the shear test as well as it was obtained experimentally using the measured peak shear stress. The laboratory data indicated that some damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Equation (1) demonstrated that during shear, JRC can be associated with shear strength. It has also been studied that after shear failure, due to the relatively low strength of the rock or applied high normal stress, the joint surface characteristics (including JRC) can be changed, and this will affect the overall shear strength of jointed rock [5,41].…”
Section: Shear Strength Of Joints Without Infillmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (1) demonstrated that during shear, JRC can be associated with shear strength. It has also been studied that after shear failure, due to the relatively low strength of the rock or applied high normal stress, the joint surface characteristics (including JRC) can be changed, and this will affect the overall shear strength of jointed rock [5,41].…”
Section: Shear Strength Of Joints Without Infillmentioning
confidence: 99%
“…Discontinuities in rock mass, including joints, bedding planes, and faults, can significantly affect the rock shear strength, resulting in slope failures [1][2][3][4][5][6][7][8]. In the field, the rock joints are typically filled with natural material such as soil.…”
Section: Introductionmentioning
confidence: 99%
“…Rock mass often contains sets of discontinues that generally undermine the overall strength and create planes of weakness (potential failure zones), and it is thus important to estimate the strength of jointed rock mass (Cui and Gratchev 2020). As several slope failures were associated with sandstone, a series of shear box tests were conducted on jointed and intact core samples of sandstone (Cui et al 2019) to study the effect of joints on rock strength. For the jointed rock specimens, the surface roughness described by the joint roughness coefficient (JRC) before and after each test was recorded and compared.…”
Section: Rock Mass Discontinuities and Strength Of Jointed Rockmentioning
confidence: 99%
“…Although grain shape and angularity are still active research topics, the study of surface roughness is one step ahead of understanding the microscopic contact-scale behavior of ballast particles. Among many other engineering applications, including contact resistance of metal surfaces, wear, contact friction, and joint rock strength [10][11][12], the study of surface roughness characteristics is equally important for railway ballast grains. This is because the roughness of individual grain surfaces affects the interparticle friction coefficient, normal stiffness, and shear modulus [13].…”
Section: Introductionmentioning
confidence: 99%